Guidance for precision landing on asteroid using active hopping trajectory - Liang, Zixuan; Lv, Chang; Zhu, Shengying; Ge, Dantong (Acta astronautica, 2022)
In the landing mission on low-gravity asteroids, the probe may have a large position error when touching the surface or hop away from the desired target after a collision. To achieve a precision landing, a guidance method using an active hopping trajectory is proposed. In contrast to passive hopping, the active hopping strategy can reduce the landing errors by controlling the collision attitude sequence of the probe. The collision attitude sequence is determined by dynamically planning the hopping trajectory which consists of an active hopping phase and a braking phase. The active hopping phase achieves an expected range with a small number of hops, and the braking phase eliminates the probe's horizontal velocity and provides feedback for the range adjustment of the active hopping phase. The guidance method based on the hopping trajectory planning is then verified in a simulated asteroid landing scenario. The results show that the method is effective in reducing the landing errors, robust to the environmental parameter perturbations, and applicable to landings on inclined surfaces. •A guidance method using active hopping trajectory is developed for the precision landing on the surface of asteroids.•The guidance method is effective in reducing the landing errors by controlling the collision attitude sequence of the probe.•The guidance method can reduce the effect of environment parameter perturbations by dynamically planning the hopping trajectory.•The guidance method is applicable to landing on asteroids with inclined surfaces.